Inteligencia emocional y convivencia de los estudiantes de básica secundaria en contextos etnoeducativos (2023)
The research entitled Emotional Intelligence and Coexistence of Secondary School students in Ethno-educational Contexts was developed with the aim of improving the coexistence of students in the Paulino Salgado Batata Educational Institution and the José Consuegra Higgins Educational Institution, since there was a high level of aggression, verbal and sometimes physical, mainly in students belonging to the Afro-Colombian community. This being so, the central idea was to strengthen the students' emotional intelligence, since not knowing their emotions and how they could manage them generated in many cases aggressive behavior, offenses even towards teachers, which is why those who present this thesis Kevin Gomez and Leonor Herrera, we set ourselves the task of finding fun and playful strategies, through which students get to know a little of how to manage their emotions and how to improve their treatment towards their classmates.